The influence of various preheating and direction of magnetic field on combustion characteristics of palm oil droplets for boiler combustion in power generation system - Dony Perdana; Mochammad Hatta; Mochammad Khoirul Rosidin; Muhamad Hanifudin (Eastern-European Journal of Enterprise Technologies, 2022)
Research has been carried out on the effect of various preheating and the direction of the magnetic field on the flame characteristics of droplet combustion. This study is important to substitute fuel from fossils with vegetable oil that is environment friendly. The variations of the magnetic field are south-south pole, north-north pole, south-north pole, north-south pole, and without. A drop of palm oil is placed on a type K thermocouple between two magnetic rods. The high-speed camera of 120fps from the front recorded the flame from the start until it went out. The researcher found out the influence of various preheating in palm oil and the magnetic characteristics and behavior of the flame. The direction of the north-south magnetic field had a higher magnetic field strength, caused the droplet combustion to increases resulting in a wider flame but a lower and more stable height compared to other magnetic field directions. The speed of combustion affected by the magnetic field intensity which resulted the flow rate of O 2 , therefore the combustion speed happened quickly because between O 2 and the fuel molecules easily react and were more flammable. The strength of the magnetic field increased oxygen concentration and fuel molecule around the reaction zone causing a short burning, resulting in a change delay time the shorter but the flame temperature increased. Stability, shape, temperature, height, delay time and combustion duration were highly valuable to design an efficient heat generator industry with the addition of magnet field. This study provides insight into the influence of magnetic field direction in magnetic field intensity on droplet combustion characteristics for boiler combustion in the power generation system